What determines the abundance of butterflies? - A short search - Ruchi, N; Nirjara, G; Sujatha, P (Recent Research in Science and Technology, 2013)
Butterflies neither seem to be identical nor abundant throughout the year. Their numbers decline over a period of time owing to harsh climatic changes or anthropological activities. Their appearance in the same place fluctuates with seasonal changes. With a view to this, abundance of some selected butterflies near the University campus in relation to the environmental factors like light, variations in temperature, humidity and rainfall was evaluated. Of the four species selected, Eurema hecabe and Catopsilia pomona (Lepidoptera: Pieridae) exhibited abundance throughout the study period while Ixias marianne (Lepidoptera: Pieridae) and Danaus chrysippus (Lepidoptera: Nymphalidae) were less abundant. Abundance was maximum during the post monsoon months, August and September. There was a positive correlation for I. marianne with minimum temperature, relative humidity and rainfall (p<0.05) while a negative correlation was observed with mean maximum temperature (p<0.05) at both places. This was also true for C. pomona from BG for mean relative humidity at evening (p<0.05). However, there is not much variation in the abundance pattern from both the places.